Recursos e Competências Organizacionais Distribuídos na Saúde Pública - Ana Maria dos Santos Carnasciali; Sergio Bulgacov (RAC: Revista de Administração Contemporânea, 2014)
This study seeks to aid understanding of the difficulties that organizations encounter when their units are geographically distributed and they seek to effectively distribute resources in accordance with geographical and demographic conditions. This study specifically looks at those segments of the population that require health services. The case study in question is representative of the decisions regarding municipal healthcare policies concerning the distribution of resources in terms of staff, material and equipment. It serves as a reference for the inherent difficulties of these decisions. The base of Geographic Information System (GIS) enables spatial and demographic analyses and their relationship with the data regarding the management of the required resources and skills. Analysis using an adapted Resource-Based View (RBV) allows evaluation of the internal decisions within the system in question. The results show the limits of the shared or isolated evaluation of the spatial distribution of resources, which are compromised by the decisions involved in these two approaches. In this sense, the concomitant evaluation of the distributed resources linked to the GIS results in an important analysis element, as it enables the identification of strategic resources that adequately satisfy the purposes of Curitiba's Municipal Health Units, in the state of Paraná.